Cardiac Stroke Volume Index Is Associated With Early Neurological Improvement in Acute Ischemic Stroke Patients - Miller, Joseph; Chaudhry, Farhan; Tirgari, Sam; Calo, Sean; Walker, Ariel P.; Thompson, Richard; Nahab, Bashar; Lewandowski, Christopher; Levy, Phillip (Frontiers in Physiology, 2021)
Early neurological improvement as assessed with the NIH stroke scale (NIHSS) at 24 h has been associated with improved long-term functional outcomes following acute ischemic stroke (AIS). Cardiac dysfunction is often present in AIS, but its association with outcomes is incompletely defined. We performed a pilot study to evaluate the association between non-invasively measured cardiac parameters and 24-h neurological improvement in prospectively enrolled patients with suspected AIS who presented within 12 h of symptom-onset and had an initial systolic blood pressure>140 mm Hg. Patients receiving thrombolytic therapy or mechanical thrombectomy were excluded. Non-invasive pulse contour analysis was used to measure mean arterial blood pressure (MAP), cardiac stroke volume index (cSVI), cardiac output (CO) and cardiac index (CI). Transcranial Doppler recorded mean middle cerebral artery flow velocity (MFV). We defined a decrease of 4 NIHSS points or NIHSS ≤ 1 at 24-h as neurological improvement. Of 75 suspected, 38 had confirmed AIS and did not receive reperfusion therapy. Of these, 7/38 (18.4%) had neurological improvement over 24 h. MAP was greater in those without improvement (108, IQR 96–123 mm Hg) vs. those with (89, IQR 73–104 mm Hg). cSVI, CO, and MFV were similar between those without and with improvement: 37.4 (IQR 30.9–47.7) vs. 44.7 (IQR 42.3–55.3) ml/m2; 5.2 (IQR 4.2–6.6) vs. 5.3 (IQR 4.7–6.7) mL/min; and 39.9 (IQR 32.1–45.7) vs. 34.4 (IQR 27.1–49.2) cm/s, respectively. Multivariate analysis found MAP and cSVI as predictors for improvement (OR 0.93, 95%CI 0.85–0.98 and 1.14, 95%CI 1.03–1.31). In this pilot study, cSVI and MAP were associated with 24-h neurological improvement in AIS.